High-Sensitive Multiwavelength Dynamic Diffuse Optical Tomography System: A Preliminary Investigation - Zhang, Limin; Cao, Bin; He, Xiangdong; Sun, Zhilong; Li, Jiao; Zhou, Zhongxing; Gao, Feng (Frontiers in Physics, 2020)
Diffuse optical tomography (DOT) is a novel functional imaging technique that has the potential clinical application for breast cancer screening. Currently, an underexploited benefit of DOT is its ability to track and characterize dynamic events related to physiological progression, which can provide additional imaging contrast. In this work, we propose a novel 3-wavelength, 32-source–detector continuous-wave dynamic DOT system that allows relatively fast and high-sensitivity imaging by combining phase lock and photon counting technologies and obtains a balance between cost and effectiveness through series parallel measurement mode. To assess the effectiveness of the proposed system prototype, we systematically investigated the key specifications of the system, including stability, channel cross talk, and dynamic range. Furthermore, the static and dynamic phantom experiments validated the capability of the system to detect the target with low absorption contrast as well as track the changes in the target’s absorption coefficient. These preliminary results indicate that the system has great application prospects in imaging of the low-contrast lesion as well as capturing the dynamic changes of hemodynamics in tumor tissue.